Evaluation of Directional Strength of SWCNT Reinforced Nanocomposites: A Finite Element Study. (2018) - Bhowmik, Krishnendu; Kumar, Pranav; Khutia, Niloy; Roy Chowdhury, Amit
Abstract: In the current work, three dimensional finite element analyses have been performed to predict the directional strength in terms of Young's modulus of carbon nanotube based composite and the results are compared with the Extended Rule of Mixtures (ERM). Square based prismatic Representative Volume Element (RVE) has been considered to model the SWCNT reinforced nanocomposite. In this study, reinforced CNT in RVE has been idealized as solid annular tube with hemispherical cap at its both ends. The parameters which are considered for these analyses are modulus ratio (ratio of Young's modulus of CNT and matrix), height fraction (ratio of CNT height and RVE length), aspect ratio (ratio of CNT height and diameter) and volume fraction of CNT. Further, different CNT diameters are also being considered in order to investigate their effects on effective Young's modulus of the composite. It is observed from the study that higher values of height fraction, modulus ratio, volume fraction and aspect ratio of CNT are beneficial to enhance the effective Young's modulus of the composite. Variation of CNT diameter does not have significant effect for high modulus ratio. However, CNT with smaller diameter leads to comparatively higher effective Young's modulus of nanocomposite in case of low modulus ratio.